Improving patient outcomes with regenerative medicine: How the Regenerative Medicine Manufacturing Society plans to move the needle forward in cell manufacturing, standards, 3D bioprinting, artificial intelligence-enabled automation, education, and training. (28th March 2020) - Hunsberger, Joshua; Simon, Carl; Zylberberg, Claudia; Ramamoorthy, Preveen; Tubon, Thomas; Bedi, Ram; Gielen, Kurt; Hansen, Caitlin; Fischer, Lynn; Johnson, Jed; Baraniak, Priya; Mahdavi, Behzad; et al.
Abstract: The Regenerative Medicine Manufacturing Society (RMMS) is the first and only professional society dedicated toward advancing manufacturing solutions for the field of regenerative medicine. RMMS's vision is to provide greater patient access to regenerative medicine therapies through innovative manufacturing solutions. Our mission is to identify unmet needs and gaps in regenerative medicine manufacturing and catalyze the generation of new ideas and solutions by working with private and public stakeholders. We aim to accomplish our mission through outreach and education programs and securing grants for public-private collaborations in regenerative medicine manufacturing. This perspective will cover four impact areas that the society's leadership team has identified as critical: (a) cell manufacturing and scale-up/out, respectively, for allogeneic and autologous cell therapies, (b) standards for regenerative medicine, (c) 3D bioprinting, and (d) artificial intelligence-enabled automation. In addition to covering these areas and ways in which the society intends to advance the field in a collaborative nature, we will also discuss education and training. Education and training is an area that is critical for communicating the current challenges, developing solutions to accelerate the commercialization of the latest technological advances, and growing the workforce in the rapidly expanding sector of regenerative medicine. : Abstract : Depicted are key areas of focus for the Regenerative Medicine Manufacturing Society. Advancing each of these areas will assist in moving the needle forward to improve patient outcomes with regenerative medicine.